1996
DOI: 10.2466/pms.1996.83.2.569
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Body Shape by Underweight, Average, and Overweight Men and Women

Abstract: Using figure drawings, perception of body shape was evaluated by underweight, average, and overweight men and women. Body-shape dissatisfaction was greatest for 60 overweight women, and about the same in 151 average weight women as it was for 102 overweight men. Average weight men (n = 107) and underweight women (n = 31) were fairly satisfied with their current shapes. Both men and women had distorted views of the shape the opposite sex found most attractive. Women guessed that men would prefer a thinner shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 1 publication
0
19
0
4
Order By: Relevance
“…In the general population, men experience much less body dissatisfaction than woman. 23,24 We found that with all patients, there were no significant differences in satisfaction or cosmesis scores between the LESS-A and CLA groups. However, in young and female patients, the satisfaction scores were significantly higher in the LESS group than the conventional group.…”
Section: Discussionmentioning
confidence: 76%
“…In the general population, men experience much less body dissatisfaction than woman. 23,24 We found that with all patients, there were no significant differences in satisfaction or cosmesis scores between the LESS-A and CLA groups. However, in young and female patients, the satisfaction scores were significantly higher in the LESS group than the conventional group.…”
Section: Discussionmentioning
confidence: 76%
“…This is consistent with the reports in the literature about gender differences. In the general population, men experience much less body dissatisfaction than women [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Ou seja, a insegurança e os sentimentos de inadequação das mesmas frente ao ambiente parecem estar associados ao seu baixo auto-conceito. Concordando com Demarest e Langer (1996), a auto-percepção da imagem corporal parece depender, em parte, do status do indivíduo diante das normas sociais e culturais aceitas.…”
Section: Discussionunclassified
“…Os dados aqui encontrados sinalizam-se também concordantes com achados da literatura envolvendo a investigação da imagem corporal de pessoas obesas, a saber, os estudos de Barros e colaboradores (1990), Cash (1993), Demarest e Langer (1996), Ogden e Evans (1996) e Werlinger, King, Clark, Pera e Wincze (1997). Esses autores constataram a presença de indicadores de insatisfação e preocupação com o corpo associados a diferentes variáveis, como a inaceitação do próprio corpo, os valores sócio-econômico-culturais e o status do sujeito.…”
Section: Discussionunclassified
See 1 more Smart Citation